Between regulatory field structuring and organizational roles: Intermediation in the field of sustainable urban development. Issue 2 (11th September 2018) - Bothello, Joel; Mehrpouya, Afshin
Abstract: Recent contributions in the domains of governance and regulation elucidate the importance of rule‐intermediation (RI), the role that organizations adopt to bridge actors with regulatory or "rulemaking" roles and those with target or "rule‐taking" roles. Intermediation not only enables the diffusion and translation of regulatory norms, but also allows for the representation of different actors in policymaking arenas. While prior studies have explored the roles that such RIs adopt to facilitate their intermediation functions, we have yet to consider how field‐level structuring processes influence (and are influenced by) the various and changing roles adopted by RI. In this study we focus on the mutually constitutive relations between field‐level change processes and the evolving roles of RIs by studying the rise of the International Council for Local Environmental Initiatives (ICLEI)/Local Governments for Sustainability, an RI serving as a bridge for sustainable urban development policies between the United Nations and local authorities. Using ICLEI as an illustrative case, we theorize four different processes of regulatory field structuration: problematization, role specialization, marketization, and orchestrated decentralization. We discuss their implications for RI roles in the field and further theorize the changing dynamics of trickle‐up intermediation processes as an RI gains power and influence.